ANTIOXIDANT ENZYMES PROFILE DURING CRYOPRESERVATION OF NILI RAVI - BUFFALO BULL SPERMATOZOA (BUBALUS BUBALIS) S. Iqbal; A. Riaz; S. Naz; M. I. Rashid Syed M. H. Andrabi; N. Ahmad (Journal of Animal and Plant Sciences, 2019)
Present study was designed to ascertain antioxidative enzyme shift during cryopreservation of buffalo bull spermatozoa. Enzymatic profile of three enzymes (catalase, superoxide dismutase and glutathione peroxidase/reductase) was established for fresh, post-dilution, pre-freezing and post-thaw stages. A total of twenty semen samples from four bulls were cryopreserved in French straws by using tris based extender. Catalase (U/mL), superoxide dismutase (U/mL) and total glutathione (µM) profile for fresh semen (25.8±1.6, 93.1±1.3, 77.4±5.2; respectively), lowered with semen extension (6.0±0.6, 60.7±2.4, 63.0±0.9 respectively; P<0.05).During equilibration time, the enzymatic profile for catalase remained stable (7.0±0.7; P>0.05) but superoxide dismutase and glutathione profile deteriorated further (47.7±1.4, 44.6±0.6 respectively; P<0.05). During cryopreservation, major shift was observed in catalase profile (2.3±0.3; P<0.05) while superoxide dismutase and glutathione readings were stable in post-thaw evaluations (P>0.05). It is concluded that cryopreservation process deteriorated catalase enzyme profile while superoxide dismutase and glutathione profiles are declined by metabolic activities of spermatozoa in time dependent manner.
Keywords: Buffalo semen; Cryopreservation; Antioxidant enzyme activity